Роман-эпопея Дмитрия Балашова «Святая Русь»: девальвация художественности под влиянием идеологии - Никольский, Евгений; Nikolskiy, Yevgeniy (Східноєвропейський національний університет імені Лесі Українки, 2015)
Роман Дмитрия Балашова «Святая Русь» анализируется в контексте биографии писателя, с точки зрения господства идеологической (почвиническо-шовинистической и евразийской) составляющей, ее явном превали¬ровании над художественностью. Отмечается, что автор прошёл путь от «певца свободы» до «адепта» авто¬ритарного строя. Данная интенция трансформировала поэтику его романов и способствовала переходу от собственно исторической прозы к неудачной попытке создать эпопею. Делаются выводы о перспективе изу¬чения исторических произведений избранного автора сквозь методологическую призму междисциплинарного синтеза. Novel by Dmitry Balashov «The holy Russia» is analyzed in the context of the biography of the writer, from the point of view of ideological domination (painiketta, chauvinism and eurasianism) component, its obvious precedence over artistry. It is noted that the author went from «singer the freedom» to «praise» authoritarian regime. This intention has transformed the poetry of his novels and contributed to the transition from a strictly historical prose to unsuccessful attempts to create an epic. In the final conclusions about the future of the study of historical works of the chosen author in the methodology of interdisciplinary synthesis.
Epic Novel by Dmitry Balashova «The holy Russia»: the Devaluation of Artistry Under the Influence of Ideology
Keywords: роман-эпопея; историческая проза; роман; жанроведение; Д. Балашов; мифологема «святой Руси»; факты и вымыслы; имагология; шовинизм; почвенничество; рашизм; художественность; the epic novel; historical fiction; romance; genre studies; Dmitry Balashov; mythologeme «Holy Russia»; facts and fictions; imagology; chauvinism; painiketta; rashism; artistry